Grain processing reduces E. coli O157 in feedlot cattle - Fox, J.T.; Jacob, M.E.; Reinstein, S.L.; Drouillard, James S.; Nagaraja, Tiruvoor G. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Escherichia coli O157 is an important food-borne pathogen for which the gastrointestinal tract of cattle is the major reservoir. Fecal shedding of E. coli O157 in cattle reflects the ability of the organism to persist in or colonize the gastrointestinal tract. Evidence suggests that the site of persistence or colonization is in the hindgut and not the rumen. Although the reasons are not known, it is likely that the ecosystem of the hindgut is more hospitable than the rumen. Therefore, we hypothesize that dietary factors that promote supply of substrates (starch, fiber, protein, or lipids) to the hindgut will have a significant effect on the ability of E. coli O157 to survive and colonize, and influence shedding in feces. Our objective was to use processed grains to alter hindgut fermentation in ways detrimental to the survival, growth, and colonization of E. coli O157. Grains that are less extensively digested within the rumen produce more starch for the hindgut, increasing fermentation activity and acid production in the hindgut. Steam-flaking of grains has been shown to enhance ruminal starch digestion compared to dry-rolling, effectively reducing the amount of starch reaching the hindgut. The objective of this study was to evaluate the effects of grain type (sorghum or wheat) and grain processing (dry-rolled or steam-flaked) in finishing diets on prevalence of E. coli O157 in cattle.
Keywords: Beef; Cattle; E. coli O157; Processed grains